1979
DOI: 10.1126/science.424760
|View full text |Cite
|
Sign up to set email alerts
|

A Brain Event Related to the Making of a Sensory Discrimination

Abstract: Event-related potentials associated with detected targets in a vigilance task were analyzed in two ways: (i) by sorting the potentials in terms of sequential reaction time bins of 50 milliseconds and (ii) by examining the single trial waveforms. A negative component (N2) covaried in latency with reaction time. These results support the hypothesis that N2 reflects a decision process which controls behavioral responses in sensory discrimination tasks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
150
4
1

Year Published

1986
1986
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 361 publications
(175 citation statements)
references
References 15 publications
14
150
4
1
Order By: Relevance
“…The late component was consistent with the time window for the N2 potential which correlates with the decision process for RT (Ritter et al, 1979). Early components (P100) were unchanged, suggesting that processes affected were for sensory discrimination and target selection.…”
Section: Vepsupporting
confidence: 67%
“…The late component was consistent with the time window for the N2 potential which correlates with the decision process for RT (Ritter et al, 1979). Early components (P100) were unchanged, suggesting that processes affected were for sensory discrimination and target selection.…”
Section: Vepsupporting
confidence: 67%
“…In contrast, the fronto-central distribution of the negativity found here is reminiscent of the scalp distribution of the N200 component that has been widely described in the ERP literature as reflecting a general mismatch effect [32,33]. The occurrence of the N200 is often linked to a subsequent positivity, P3a, and forms the N2-P3a complex, which has been shown to develop in response to surprising, unexpected stimuli.…”
Section: Discussionsupporting
confidence: 52%
“…For example, a response associated with incomplete evaluation of the stimulus may lead to a lower P300 latency/RT correlation (Magliero et al 1984). Additionally, speed vs. accuracy instructions (Kutas et al 1977;McCarthy and Donchin 1983;Pfefferbaum et al 1983) and factors of task difficulty (Ritter et al 1979;Hillyard and Kutas 1983) can affect the observed association between ERP component latency and RT.…”
Section: Discussionmentioning
confidence: 99%